Synthesis and evaluation of the antitumor potential of new aminated or methoxylated di(hetero)arylthioethers in the thieno[3,2-b]pyridine series - Calhelha, Ricardo C. (2013)
Synthesis and evaluation of the antitumor potential of new aminated or methoxylated di(hetero)arylthioethers in the thieno[3,2-b]pyridine séries. In 1st Symposium on Medicinal Chemistry. Braga Several thienopyridines have already been described as inhibitors of cell proliferation using human tumor cells[1,2], highlighting the interest of studying their antitumorpotential. ln this work, we present the synthesis of di(hetero)arylthioethers 1a-fby SNAr of the 7-chloro thieno[3,2- b]pyridine with amino or methoxy thiophenols in good to high yields, like presented in the scheme.